The effect of jump topspin serve speed on reception quality in men`s volleyball - Petru, J.; Vencúrik, T. (Physical Activity Review, 2024)
Background: The essential activities contributing to winning a volleyball game are serve, offense, and block. The study aimed to determine if the increasing speed of the jump topspin serve negatively affects the reception quality.